210-year ice core records of dust storms, volcanic eruptions and acidification at Site-J, Greenland (scientific note) - Fujii, Yoshiyuki; Kamiyama, Kokichi; Shoji, Hitoshi; Narita, Hideki; Nishio, Fumihiko; Kameda, Takao; Watanabe, Okitsugu (2001)
P(論文) 210-year records of dust concentration, electrical conductivity, acidity (pH), non-sea salt sulfate (nss sulfate) and nitrate concentrations were obtained for an ice core from Site-J, Greenland. The ice core was well dated by counting annual cycles of the δ^<18>O profile and by tuning with time markers established for tritium peaks and the Laki 1783 eruption signal. Dust records in both ice cores from Site-J and Crete suggest that dust storms occurred in 1818,1900,1919,1936 and 1943 over Greenland. Electrical conductivity shows remarkable peaks probably due to volcanic eruptions with VEI larger than 4. The anthropogenic effect on precipitation chemistry started in ca. 1860,40 years earlier than the time previously reported. Nss sulfate increased remarkably, much more than nitrate, because of the rapid increase in solid fossil fuel combustion, but by the early 1970's, the nitrate concentration exceeded the nss sulfate concentration due to the intense increase in liquid fossil fuel combustion since the 1950's. The decrease in sulfate and nitrate concentrations started in the early 1970's. This is attributed to the spread of suppression facilities for anthropogenic pollutants emitted by the combustion of solid and liquid fossil fuels. departmental bulletin paper